Different spectrophotometric methods for simultaneous quantitation of Vericiguat and its alkaline degradation product: a comparative study with greenness profile assessment - Doaa M. Mustafa; Nancy Magdy; Noha F. El Azab (Scientific Reports, 2023)
Abstract Investigations concerning novel drugs and their induced degradation products are necessary for clinical research and quality control in the pharmaceutical industry. Four spectrophotometric techniques have been performed for simultaneous quantitation of Vericiguat (VER) and its alkali-induced degradation product (ADP) without prior separation. Method A is a dual wavelength method (DW) that estimates the absorbance difference at 314–328 nm, and 246–262 nm for VER and ADP; respectively. Method B uses a ratio difference method (RD) to estimate the ratio spectrum’s amplitude difference (DP318-342) and (DP284-292) for VER and ADP; respectively. Method C uses a first derivative ratio method (1DD) to estimate the peak ratio spectrum amplitude of the first derivative at 318 and 275 nm for VER and ADP; respectively. Method D uses the mean centering of the ratio spectra (MCR) to estimate amplitude values for VER and ADP at 337 and 292 nm; respectively. In a concentration range of 5.00–50.00 µg/mL for VER and 5.00–100.00 µg/mL for ADP, the methods were validated following ICH criteria and utilized to estimate VER in bulk and its dosage form. The methods’ greenness was assessed via three tools: the green analytical procedure index (GAPI), analytical eco-scale, and analytical greenness assessment (AGREE).